Genomic medicine for cancer prognosis. Issue 1 (11th August 2014) - Mathur, Aarti; Zeiger, Martha A.
<x xml:space="preserve">Abstract</x> There is a heavy research emphasis on prognostic and predictive approaches based on genomic data, which has in turn challenged standard paradigms for the management of patients with malignant disease. This review will highlight the recent advances made in genomic medicine, specifically with regard to prognosis associated with thyroid cancer, cutaneous melanoma, and pancreatic adenocarcinoma. Although none of the markers reviewed have been incorporated into routine clinical practice, this review covers the most promising ones. J. Surg. Oncol. 2015 111:31–37. © 2014 Wiley Periodicals, Inc.